Karakteristik Wilayah Sebagai Determinan Penyebaran Malaria di Kabupaten Jepara - Raharjo, Mursid; Sutikno, Sutikno; Mardihusodo, Sugeng Juwono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2003)
ABSTRACT Background : Malaria in Jepara district is inequitable distribution. This is very important object specially to evaluate the correlation between the geographical characteristics and the Anopheles aconitus densities as a vector of malaria. The other object is the correlation between the climatic changes and malaria incidence. Method : Based on the malaria incidence the area are segregated in 3 class, High Case Incidence (HCI), Medium Case Incidence(MCI), and Low Case Incidence (LCI). The next stratification was based on topography, with the interval of 0-25 m, 26 –50 m, 51-75 m, 76 – 100 m, and more than 100 m above sea level. Research was done in the wet and dry season. Correlation between dependent and independent variable analyses by the Pearson Product Moment, and determinant coefficient analyses to conclude the determinant variable Result : The results of the research showed determinant coefficient of geographical characteristics to Anopheles aconitus densities 94,9% (R2 =0,949), with the correlation coefficient 0,974. Gradually the partial impact of the geographical characteristic to the Anopheles aconitus densities were : 1. humidity 64,96% 2.waste water treatment 36,6%; 3. solid waste management 32,15%; 4. salinity 23,33%; 5. population density 19,18%; 6.air temperature 16,48%; 7. topography 11,56%; 8. vegetation densities 5,2%, if the other parameter do not calculated. Conclusion: Jepara district have deferent geographical characteristic that fluctuatively as the season, and regulated Anopheles aconitus distribution. The determinant parameter are humidity (64,96%), waste water treatment (36,6%) solid waste management (32,15%); salinity (23,33%,), population density (19,18%) air temperature (16,48%), topography (11,56%) vegetation densities 5,2%, if the other parameter do not calculated. The geographical characteristic compose the special zone as a Anopheles aconitus habitat. Key word : Geographical characteristic, Anopheles aconitus densities, determinant parameter.